Uncover the amazing world of needlework and sewing through app - Chua, Jing Yi (Nanyang Technological University, 2023)
This report presents the development and evaluation of the mobile app designed to enhance the learning experience of beginner needlework enthusiasts. The app provides a platform for users to infer needlework information and techniques at their own pace and convenience and offers a range of features and functionalities to support their learning journey. This project aims to create a mobile application to provide information about needlework for enthusiasts to access conveniently.